Electric field-induced rupture kinetics of giant unilamellar vesicles with varying gramicidin A content in membrane - Md. Tariqul Islam Bhuiyan; Mir Jubair Ahamed; Rajia Sultana; Tawfika Nasrin; Md. Kabir Ahamed; Md. Masum Billah; Mohammad Abu Sayem Karal (PLoS ONE, 2026)
In this study, we examine the rupture kinetics of giant unilamellar vesicles (GUVs) composed of DOPG/DOPC and varying mole fractions of gramicidin A (GrA), under externally applied electric fields. Time-resolved fluorescence microscopy reveals that the presence of GrA modulates vesicle rupture behavior in a non-monotonic fashion. At lower contents of GrA (0–0.05 mole%), GUVs exhibit enhanced structural resilience, with significantly reduced rupture probability, suggesting increased membrane stability. However, at higher contents of GrA (0.05–5%), vesicles display accelerated rupture kinetics, reflecting decreased membrane integrity. Quantitative analysis of rupture events indicates a biphasic dependence of the rupture rate constant on GrA content. The pore-edge tension was obtained from the slope of the fitted linear relation between the logarithm of the rupture rate constant and the inverse of effective membrane tension for different GrA%. The pore-edge tension varies nonlinearly with GrA%, reaching a minimum at intermediate GrA levels (0.05%). These findings are consistent with a theoretical model for electroporation, where pore formation is governed by a balance between destabilizing electric tension and stabilizing line tension. The results highlight how lower mole% of GrA enhance membrane mechanical robustness, while excessive GrA incorporation disrupts bilayer cohesion and accelerates electroporation. This study provides new insights into the tunable electromechanical properties of lipid membranes modulated by membrane-active peptides.